Microstructure and unusually strong recrystallization texture of the FCC phase of a cost-effective high-strength dual-phase AlCrFe2Ni2 high entropy alloy. (June 2022) - Tripathy, B.; Saha, R.; Bhattacharjee, P.P.
Abstract: The evolution of microstructure and recrystallization texture was investigated in a severely deformed (90% cold-rolled) and annealed (FCC + BCC/B2) AlCrFe2 Ni2 high entropy alloy (HEA) with an exclusive focus on the FCC phase. Cold-rolling resulted in pronounced bending and folding of the lamellae, progressive alignment of the phases along the RD, large misorientation gradient in the FCC phase, and finally ultrafine structure formation. The FCC phase showed a predominantly brass-type (B) texture with orientations spreading from the G (011<100>) to B (011<112>), indicating its low stacking fault energy (SFE). The prior cold-rolling deformation strongly influenced the annealing behavior, including lamellar to microduplex structure, grain boundary character evolution, and faster attainment of equilibrium phase fractions. The 90% cold-rolled and annealed material revealed the presence of a remarkably strong B component, unlike the weak recrystallization texture of typical FCC single-phase low SFE HEAs. The origin of the strong B recrystallization component was attributed to a combined effect of the high misorientation gradient in the FCC phase, increased boundary mobility at high annealing temperatures, and the presence of the BCC/B2 phase inhibiting grain growth and thus preserving the recrystallized B grains. The tensile properties of the HEA were evaluated to highlight the outstanding cost-performance advantage of the alloy. Highlights: Effect of prior strain on microstructure and texture of annealed AlCrFe2 Ni2 investigated. Development of brass-type (011<112>) texture after heavy cold-rolling. Prior-strain dependent microstructural transformation after annealing. Development of unusually strong brass component after annealing. The strong brass texture after annealing is at variance with that reported for HEAs.